Impact of ESG score on Company Performance in Nordic Countries - Hoque, Mohammad (My University, 2025)
This thesis analyzes the relationship between ESG scores and financial performance of the publicly listed Nordic companies from 2014 and 2023. The research uses a panel data set of 187 companies and 1, 363 firm-year observations to describe how a total ESG performance and its components (environmental, social and governance) influence ROA and ROE. The study uses fixed-effects regression models to explore contemporaneous and lagged effects. The models are controlled with the firm size, leverage, growth, and price-to-book ratio. The findings show a positive and statistically significant relationship between the overall ESG Score and ROA, and environmental dimension has the strongest positive association. Nevertheless, there is no clear relationship between both ESG metrics and ROE in the contemporaneous models. Remarkably, lagged analysis showed dominant negative (but largely insignificant) ESG-financial performance relationships. Which is contrary to the expectation that ESG payoffs happen over long periods of time. These results suggest that, in Nordic markets ESG initiatives will have quicker operational benefits instead of long-term effects. The study contributes to the conceptual framework of stakeholder theory, resource-based view, and institutional theory. It presents the practical aspects of sustainable investment strategies in mature ESG markets. The results emphasize importance of the disaggregated ESG analysis and the effect of the institutional context on ESG-financial performance relations.
Keywords: finance; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance